2013
DOI: 10.1523/jneurosci.0342-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Short- and Long-Term Brain Pathology and Long-Term Behavioral Deficits in Male Repeated Hypoxic Rats Closely Resembling Human Extreme Prematurity

Abstract: Brain injury in the premature infant is associated with a high risk of neurodevelopmental disability. Previous small-animal models of brain injury attributable to extreme prematurity typically fail to generate a spectrum of pathology and behavior that closely resembles that observed in humans, although they provide initial answers to numerous cellular, molecular, and therapeutic questions. We tested the hypothesis that exposure of rats to repeated hypoxia from postnatal day 1 (P1) to P3 models the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 52 publications
4
37
0
Order By: Relevance
“…There are several reports exploring the role of experimental intermittent hypoxemia in neurologic morbidity associated with adult sleep apnea and apnea of prematurity (Cai et al, 2011(Cai et al, , 2012Douglas et al, 2010;Oorschot et al, 2013;Xu et al, 2004). Similar to our results, studies on neonatal animals demonstrated poorer WM myelination in mice and rats exposed to IH compared to their naïve controls.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…There are several reports exploring the role of experimental intermittent hypoxemia in neurologic morbidity associated with adult sleep apnea and apnea of prematurity (Cai et al, 2011(Cai et al, , 2012Douglas et al, 2010;Oorschot et al, 2013;Xu et al, 2004). Similar to our results, studies on neonatal animals demonstrated poorer WM myelination in mice and rats exposed to IH compared to their naïve controls.…”
Section: Discussionsupporting
confidence: 90%
“…In this paradigm the cumulative duration of hypoxic exposure reached 25% of each 24 h time-period. In another report hypoxic exposure was relatively short (three days), but very severe (1.5% O 2 for 15 min, seven events a day) (Oorschot et al, 2013). This may explain a significant loss of precursors of myelin-producing cells observed in the above referenced model and hippocampal and cortical neuronal loss in the IH-models by Douglas et al (2010) and Gozal et al (2001).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations